2017
DOI: 10.1038/s41467-017-02083-1
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite DNA-harbouring vesicles activate cytosolic immune sensors

Abstract: STING is an innate immune cytosolic adaptor for DNA sensors that engage malaria parasite (Plasmodium falciparum) or other pathogen DNA. As P. falciparum infects red blood cells and not leukocytes, how parasite DNA reaches such host cytosolic DNA sensors in immune cells is unclear. Here we show that malaria parasites inside red blood cells can engage host cytosolic innate immune cell receptors from a distance by secreting extracellular vesicles (EV) containing parasitic small RNA and genomic DNA. Upon internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
228
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 160 publications
(237 citation statements)
references
References 72 publications
8
228
0
1
Order By: Relevance
“…Cells were imaged using an inverted confocal microscope or multispectral IFC (ImageS-treamX Mark II imaging flow cytometer; Amnis Corp, Seattle, WA, part of EMD Millipore) as previously described in Sisquella et al [88]. As a control, the unused schistosomal-growing medium was also labeled.…”
Section: Ev Labeling and Facs Analysismentioning
confidence: 99%
“…Cells were imaged using an inverted confocal microscope or multispectral IFC (ImageS-treamX Mark II imaging flow cytometer; Amnis Corp, Seattle, WA, part of EMD Millipore) as previously described in Sisquella et al [88]. As a control, the unused schistosomal-growing medium was also labeled.…”
Section: Ev Labeling and Facs Analysismentioning
confidence: 99%
“…It has recently been revealed that, in addition to RNA and proteins, vesicles from different eukaryotic systems also harbor DNA molecules. The size of the vesicular DNA, from both eukaryotic and prokaryotic origin, typically ranges from hundreds of bp to over 20 kb and its source can be chromosomal, episomal, or even mitochondial . These exciting discoveries raise the possibility that secreted vesicles can serve as mediators of genetic material exchange among microbes, thus offering a potential explanation for observed HGT events between eukaryotic cells.…”
Section: Secreted Vesicles As Dna Freighters and Possible Mediators Omentioning
confidence: 99%
“…A malaria study revealed that, in fact, the eukaryotic parasite delivers vesicles harboring not just episomal genes, but also parasitic genomic DNA . Further support for an EV‐mediated HGT event in malaria comes from a study by Sundararaman and co‐workers .…”
Section: Secreted Vesicles As Dna Freighters and Possible Mediators Omentioning
confidence: 99%
“…In support of these observations, P. falciparum iRBCs‐derived EVs have been shown to stimulate the cells of the innate immune system in vitro by activating a proinflammatory and anti‐inflammatory cytokine response in macrophages and by strongly activating neutrophils to spontaneously move even in the absence of a chemotactic gradient (Mantel et al, ). Recently, Regev‐Rudzki and colleagues revealed a previously unidentified aspect: P. falciparum strains deliver genomic DNA via EVs to alter the immune response (Sisquella et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, microvesicles are formed by budding and shedding from the plasma membrane and are larger with greater size heterogeneity. EVs carry diverse content such as RNA (Baglio et al, ; Ridder et al, ), DNA (Sansone et al, ; Sisquella et al, ; Thakur et al, ), proteins (Simpson, Lim, Moritz, & Mathivanan, ; Torrecilhas, Schumacher, Alves, & Colli, ), and lipids (Record, Silvente‐Poirot, Poirot, & Wakelam, ; Verderio, Gabrielli, & Giussani, ), which can be delivered to target cells.…”
Section: Introductionmentioning
confidence: 99%